2018
DOI: 10.2147/copd.s177038
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge extended care contributes to the disease control of patients with COPD: a Chinese study

Abstract: BackgroundThe aim of this study was to evaluate the efficacy of extended care in patients with COPD.Patients and methodsA total of 140 patients with GOLD-2 to -4 of COPD were included in final analysis. The care efficacy was evaluated by the St George’s Respiratory Questionnaire 12-item General Health Questionnaire (GHQ-12), pulmonary function test and blood gas analysis.ResultsThe extended care improved the activity ability of COPD patients, relieved the clinical symptoms as well as reduced the impact degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…3,4 Previous studies indicate that extended care health education can help children and their parents to establish correct oral behavioural habits and reduce the incidence of caries. [5][6][7] Ye and Li 8 found that the effect of extended care is influenced by patient participation. Clinical nursing staffs have focused on combining extended care health education measures with patient participation.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies indicate that extended care health education can help children and their parents to establish correct oral behavioural habits and reduce the incidence of caries. [5][6][7] Ye and Li 8 found that the effect of extended care is influenced by patient participation. Clinical nursing staffs have focused on combining extended care health education measures with patient participation.…”
Section: Introductionmentioning
confidence: 99%